(untitled) (Research, Society and Development, 2022)
It is known that the disorders arising from the increase in the use of drugs, especially cocaine, are increasing, since it has differentiated use patterns, making it difficult to fight. Epidemiological data on this topic are still scarce and insufficient and, observing this fact, the present study proposes to contribute to research in the area addressing cases of cocaine seizure through spatial analysis in the municipality of Campina Grande, Paraíba, for the year 2018. This is a descriptive, cross-sectional, retrospective and quantitative study, using data from the Forensic Laboratory Nucleus of Campina Grande of the Scientific Police Institute (NULF-CG / IPC), and of the files filed with the Narcotics Court of the District of Campina Grande. Categorical variables were presented using descriptive statistics and for data analysis and treatment, the chi-square test and Fisher’s exact test were used considering 5% of the significance level (p <0.05). The sample revealed the main sociodemographic characteristics of the users (men, browns, singles, between 20 and 40 years old, with elementary education, unemployed); the seizures corresponded, predominantly, to trafficking in the forms of "crack" and cocaine. Among the 49 official neighborhoods in the city, it was found that the most expressive neighborhoods in relation to the number of seizures were José Pinheiro, Pedregal, Serrotão and Jeremias, places considered more peripheral in the city. In view of the evidence presented here, the aim is to contribute data to increase public policies, directing the specific demands of this population, strengthening various objectives proposed by SISNAD to prevent drug use.